Imaging the Bone-Immune Cell Interaction in Bone Destruction - Hasegawa, Tetsuo; Kikuta, Junichi; Ishii, Masaru (Frontiers in Immunology, 2019)
Bone is a highly dynamic organ that is continuously being remodeled by the reciprocal interactions between bone and immune cells. We have originally established an advanced imaging system for visualizing the in vivo behavior of osteoclasts and their precursors in the bone marrow cavity using two-photon microscopy. Using this system, we found that the blood-enriched lipid mediator, sphingosine-1-phosphate, controlled the migratory behavior of osteoclast precursors. We also developed pH-sensing chemical fluorescent probes to detect localized acidification by bone-resorbing osteoclasts on the bone surface in vivo, and identified two distinct functional states of differentiated osteoclasts, “bone-resorptive” and “non-resorptive”. Here, we summarize our studies on the dynamics and functions of bone and immune cells within the bone marrow. We further discuss how our intravital imaging techniques can be applied to evaluate the mechanisms of action of biological agents in inflammatory bone destruction. Our intravital imaging techniques would be beneficial for studying the cellular dynamics in arthritic inflammation and bone destruction in vivo and would also be useful for evaluating novel therapies in animal models of bone-destroying diseases.